2008
DOI: 10.1002/art.23447
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for cytotoxic effects of anti–tumor necrosis factor agents on transmembrane tumor necrosis factor α–expressing cells: Comparison among infliximab, etanercept, and adalimumab

Abstract: Objective. Three anti-tumor necrosis factor ␣ (anti-TNF␣) agents have been proved to be effective for rheumatoid arthritis (RA) and other inflammatory disorders. Infliximab and adalimumab have been generated as anti-TNF␣ monoclonal antibodies, while etanercept is engineered from human type II TNF receptors. In spite of all 3 agents' equal efficacy for RA, both infliximab and adalimumab are effective for other diseases such as Crohn's disease and Wegener's granulomatosis, while etanercept is not. We undertook t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
220
1
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 327 publications
(238 citation statements)
references
References 38 publications
(42 reference statements)
5
220
1
4
Order By: Relevance
“…In a murine model of chronic TB, neutralization of TNF by antibody but not the TNFR fusion molecule exacerbated chronic TB because of better penetration of antibodies into granulomas (19). In humans, higher avidity and better stability of membrane-bound TNF was demonstrated with anti-TNF mAb (20), which in some studies leads to more efficient apoptosis (21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…In a murine model of chronic TB, neutralization of TNF by antibody but not the TNFR fusion molecule exacerbated chronic TB because of better penetration of antibodies into granulomas (19). In humans, higher avidity and better stability of membrane-bound TNF was demonstrated with anti-TNF mAb (20), which in some studies leads to more efficient apoptosis (21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…This may prevent or lessen the rate of apoptosis of immunocompetent cells [35,36]. A previous report showed that infliximab and adalimumab, but not ETN, induced apoptosis and cell-cycle arrest in T-cells transfected with transmembrane TNF-a [37]. These findings suggest that different anti-TNF-a therapies have different biologic effects on transmembrane TNF-a.…”
Section: Discussionmentioning
confidence: 90%
“…None of the 3 agents induced complement-dependent cytotoxicity when bound to activated human PBMC 3 . In contrast, induction of complement-dependent cytotoxicity in TNF-transfected cell lines has been reported for infliximab and adalimumab but not for etanercept [3][4][5] . Further, adalimumab or infliximab induced antibody-dependent cellular cytotoxicity (ADCC) much more potently than etanercept 6 .…”
Section: To the Editormentioning
confidence: 88%
“…Avidity of binding to soluble TNF was 10-to 20-fold greater for etanercept than for adalimumab or infliximab 3 . All the anti-TNF agents bound to membrane TNF-α on Jurkat cell lines 4 . On the other hand, binding of these agents to membrane TNF in human peripheral blood mononuclear cells (PBMC) under conditions that are more similar to those in patients showed that infliximab and etanercept had lower affinities/avidities for membrane TNF than adalimumab 3 .…”
Section: To the Editormentioning
confidence: 99%